PENGARUH BABY SPA TERHADAP PERKEMBANGAN BAYI USIA 3-9 BULAN DI PUSKESMAS SOCAH BANGKALAN - Nailufar Firdaus (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
Development is important for the child'sdevelopment phase. In the preliminary study,60% of 3-9 months infants experienceddevelopmental delays. The purpose of thestudy was to analyze the differences in thedevelopment of infants aged 3-9 monthsbefore the baby spa was conducted with thebaby spa at the Puskesmas SocahBangkalan. The study design used Pre Experimentalwith the approach of one group pretestposttest. The dependent variable is thedevelopment of infants aged 3-9 months andthe independent variable is baby spa. Thepopulation of all infants aged 3-9 months whowere not sick was 25 infants with a sample of16 infants grouped into one group and carriedout baby spa treatment, with a purposivesampling technique. The instruments usedKPSP sheets were then analyzed usingunivariate analysis using the Paired SampleT-Test statistical test. Based on the results of a study beforebaby spa that most babies (62.4%) haddeveloped doubts as many as 10 babies.while after baby spa (50%) babies developdubious development and (50%) theremaining babies develop accordingly, namely8 babies, Statistical test results with PairedSamples developmental T-Test for infantsaged 3-9 months before and after baby spa pValue (0,000) <α (0.05) means that there is adifference in the development of infants aged3-9 months before and after the baby spa. We recommend that health workers canalso do baby spa because baby spa is verybeneficial for children's development.